A prevenção criminal através do espaço construído (CPTED) em Portugal: revisão da literatura e redes de conhecimento = Crime prevention through environmental design (CPTED) in Portugal: literature review and knowledge networks - Saraiva, Miguel Marinho (2019)
Although Crime Prevention Through Environmental Design (CPTED) has been recognized as an effective mean to reduce feelings of insecurity and crime rates, in Portugal it is still mostly unknown, scarcely used in urban projects and absent from law decrees and academic training. Portuguese research on CPTED has a little over a decade, and is divided into the academia, the administration and the police, with variable degrees of integration and transferability. This article aims to be the first comprehensive study concerning the evolution of this discipline in Portugal. For that an extensive and chronological literature review is performed and a co-authorship knowledge network is devised. From an initially dispersed and closed model, research has evolved in the last few years to an integrated model, with important bridges being raised between the various institutional groups.